New insights into defluoridation via induced crystallization: Implications of phosphate species regulation for process efficiency and economics - Deng, Linyu; Wang, Yuan; Yang, Haolan; Zhang, Ruiyi; Huang, Tinglin (Separation and purification technology, 2024)
[Display omitted] •F and P in the effluent were 0.45 and 0.05 mg·L−1 with mixed phosphates precipitant.•Two F removal pathways are F + P + Ca → FAP and OH + P + Ca → HAP + F → FAP.•Phosphate species regulation is both simple and chemical cost-saving.•Seeds could be regenerated by peeling precipitates from them by natural drying.•Recovered precipitates FAP have potential for application in phosphate industry. Excess fluoride (F) at low concentrations in groundwater remains a challenge. F removal via fluidized-bed induced crystallization has been receiving increasing attention; however, the precipitant cannot be fully utilized. This results in generation of by-products, inadvertently increases the treatment cost, and impedes the assessment of product purity. In this study, phosphate species regulation was employed to improve the F removal efficiency without decreasing the phosphate utilization efficiency. It shows that F concentration could be reduced from 4.75 to 0.45 mg·L−1, with P concentration in the effluent being only 0.05 mg·L−1 at a P:F molar ratio of 3, involving appropriately mixed phosphate species. Hydroxyapatite (HAP) crystallization, subsequent F adsorption, and directly induced fluorapatite (FAP) crystallization occurred simultaneously in the fluidized bed, which was indirectly confirmed through intermittent operation of the process. The products of the induced crystallization process were FAP and a small amount of HAP, as determined qualitatively using X-ray diffraction (XRD), scanning electron microscopy (SEM), and Fourier-transform infrared spectroscopy (FTIR) tests. Overall, by regulating the phosphate species, the F removal efficiency is maintained, the cost of the precipitant is lowered, and the residual P concentration in the effluent is reduced. The process results in products with FAP as the main component, which can be used as raw material for the phosphoric acid purification process.